2017
DOI: 10.1002/pc.24481
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of epoxy resin composites filled with combustion‐synthesized AlN powder

Abstract: The thermal conductivity of epoxy resin composites filled with combustion‐synthesized aluminum nitride (AlN) particles was investigated. The mixing of the composite constituents was carried out by either a dry method (involving no use of solvent) for low filler contents or a solvent method (using acetone as solvent) for higher filler contents. It was found that surface treatment of the AlN particles using a silane, 3‐aminopropyltriethoxysilane (APTES), increases the thermal conductivity of the resultant compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…When the amount of added AlN was between 10–20 wt%, the sheets’ thermal conductivities increased rapidly, because AlN particles are evenly dispersed in the matrix ER and 9-DG-ER, respectively, forming a continuous thermally conductive network structure. When the amount of added AlN was 20 wt%, the λ values of the AlN/DG-ER sheet and the AlN/ER sheet reached 1.31 and 0.83 W·m −1 ·K −1 , respectively, and the λ value of the AlN/DG-ER sheet was higher than previously reported [ 43 , 44 ]. When the amount of AlN was further increased, the λ values of both the AlN/DG-ER sheet and the AlN/ER sheet increased more slowly.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…When the amount of added AlN was between 10–20 wt%, the sheets’ thermal conductivities increased rapidly, because AlN particles are evenly dispersed in the matrix ER and 9-DG-ER, respectively, forming a continuous thermally conductive network structure. When the amount of added AlN was 20 wt%, the λ values of the AlN/DG-ER sheet and the AlN/ER sheet reached 1.31 and 0.83 W·m −1 ·K −1 , respectively, and the λ value of the AlN/DG-ER sheet was higher than previously reported [ 43 , 44 ]. When the amount of AlN was further increased, the λ values of both the AlN/DG-ER sheet and the AlN/ER sheet increased more slowly.…”
Section: Resultscontrasting
confidence: 59%
“…Jiao et al [ 43 ] have achieved λ values in an epoxy composite of 0.42 W·m −1 ·K −1 by adding 17.6 vol% of AlN. Chung and Lin [ 44 ] have reported that, after adding 20 vol% of AlN to their epoxy composite, the λ value of the composite was about 0.6 W·m −1 ·K −1 . Figure 6 a presents a comparison of thermal conductivities for the AlN/DG-ER sheet and the AlN/ER sheet at the same amounts of added AlN addition.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al 35 proposed a CPCM combined with poly(ethylene glycol), silica gel, and β-AlN powder to enhance the thermal conductivity further. Chung et al 36 increased the thermal conductivity of epoxy resin composites with AlN powers; the experimental results revealed that AlN fillers played a virtual role in enhancing the thermal conductivity of composites.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Most polymers are both thermally and electrically insulative and the incorporation of thermally conductive fillers into polymers is thought to be a cost-effective method to suit the increasing needs of efficient thermal dissipation materials in the aeras of power electronics, heat exchangers and heat sinks among others. [4][5][6] The commonly employed fillers include: carbonaceous fillers such as graphite, [7,8] carbon nanotubes (CNT), [9] graphene, [10] carbon fibers [6,11,12] ; metallic fillers such as copper, [13] silver, [14] aluminum [15] and steel fibers [16,17] ; ceramics fillers such as hexagonal boron nitride (BN), [18,19] aluminum nitride, [20] and silicon nitride, [21] alumina. [22] Ceramic fillers have been widely employed to fabricate both thermally conductive and electrically insulating polymer composites, which exhibits potential applications in the fields of packaging and battery units for electronics as well as alternative fuel vehicles.…”
Section: Introductionmentioning
confidence: 99%